A Survey of the Role of Environmental Education in Biodiversity Conservation in the Greater Accra Region of Ghana - Fatima Eshun; Richard Kwasi Wotorchie; Alfred Aninkorah Buahing; Ann Afua Harrison-Afful; Wonder Kofi Atiatorme; Gloria Amedzake; Yaw Adofo-Yeboah; Vicentia Mante (Conservation, 2022)
Biodiversity in all its forms has come under threat. The rate of biodiversity loss has attracted global attention, and most governments are trying to put measures into place to reduce the rate of loss. One way to ensure that people are conscious of biodiversity conservation is through education. However, studies on creating awareness for biodiversity conservation have received less attention in the literature. To address this knowledge gap, this study used questionnaires to investigate the role of education in biodiversity conservation in the Greater Accra Region of Ghana. The study found that environmental education, particularly an awareness of biodiversity conservation, is critical for conserving biodiversity. However, people’s knowledge of biodiversity conservation is too weak or inadequate to motivate them to incorporate biodiversity conservation practices into their daily activities. Furthermore, understanding the importance of biodiversity conservation comes with an increase in age. Increasing education on biodiversity conservation at an early age can help people become more aware of biodiversity conservation as they age, and they can incorporate it into their daily activities to reduce biodiversity loss. The study calls for a revision of the environmental education syllabus at various levels, particularly the basic and SHS levels, including more practical topics to help people change their attitudes and perceptions and incorporate biodiversity into their daily activities.